Robust tracking control for wheeled mobile robot based on extended state observer. (2nd January 2016) - Yang, Hongjiu; Fan, Xiaozhao; Xia, Yuanqing; Hua, Changchun
Abstract : This paper presents a new control scheme on trajectory tracking of wheeled mobile robot with nonholonomic constraints. Extended state observer is introduced to estimate unknown disturbances and velocity information. A robust tracking controller is designed to implement the accurate trajectory tracking and disturbance compensation. By theoretical, position and velocity tracking errors of wheeled mobile robot are proven uniformly ultimately asymptotically stable. Simulation results are given to illustrate the effectiveness of the developed technique. Graphical Abstract: